A case report of atypical teratoid/rhabdoid tumor and pituitary adenoma collision tumor in the sellar region - Li, Qing; Wang, Li; Chen, Yang; Luo, Rui; Wu, Jian-shan; Li, Ying; Li, Ping-ping (Frontiers in Surgery, 2025)
Collision tumor in the sellar region is extremely rare, and atypical teratoid/rhabdoid tumor (AT/RT) in the sellar region combined with pituitary adenoma has not been reported in the literature. AT/RT is a rare embryonal tumor of the central nervous system with extremely high malignancy and diverse histological morphology. The tumor cells can differentiate into primitive neuroectodermal, mesenchymal, or epithelial lineages and are characterized by rhabdoid cells. AT/RT mostly occurs in children, and its incidence in adults is extremely low. Here, we report a case of a collision tumor in the sellar region consisting of an atypical teratoid/rhabdoid tumor and a pituitary adenoma. The patient was a 33-year-old female who first presented with a headache for seven days and decreased vision in the left eye for four days. The initial imaging diagnosis was invasive pituitary macroadenoma, and partial resection of the pituitary lesion was performed under neuroendoscopy through the nasal cavity and sphenoid sinus. Postoperative pathology revealed the coexistence of an atypical teratoid/rhabdoid tumor and a pituitary adenoma. The diagnosis of AT/RT is challenging due to the patient's very uncommon age, non-specific imaging findings, unusual histological pattern, and complex tissue composition.